Analisis Efektivitas dan Efisiensi Pengelolaan Dana Desa Dalam Meningkatkan Kesejahteraan Masyarakat (Studi Kasus: Desa Dewa Djara Kabupaten Sumba Tengah - Rambu Sedu Oyi; Sodik Sodik; Endah Puspitosarie (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
Village Fund management holds a strategic role in supporting rural development and improving community welfare; however, in many areas, including Dewa Djara Village, Central Sumba, its effectiveness and efficiency remain a challenge. This study aims to answer the main question of how far the Village Fund is managed effectively and efficiently and how it impacts community welfare. Using a descriptive qualitative design combined with financial ratio analysis, data were collected through documentation of the Village Budget (APBDes) and interviews with village officials and residents. The findings reveal that Village Fund management in Dewa Djara Village is still ineffective due to the low achievement of development goals, while its efficiency is considered pseudo as it mainly results from low budget absorption rather than actual savings. The main obstacles include delayed disbursement, limited human resource capacity, lack of transparency, and low community participation. These results highlight the need for accountable, transparent, and participatory financial governance to ensure the Village Fund truly contributes to community welfare. This research recommends strengthening the capacity of village officials, implementing stricter oversight mechanisms, and encouraging broader community involvement, while also providing a basis for future studies on more sustainable village financial management strategies.